The Determinant Factors of E-Loyalty in Customer-to-Customer E-Commerce Moderated by Gender - Fernanda Losaura; Putra Iyang Bodronoyo; Dimas Tri Wibowo (The Winners, 2022)
E-commerce businesses dealt with one of the most important challenges, which was to create personalized e-loyalty for their customers to stay loyal to their e-commerce platform. The research used the 8C's framework developed to determine the effect of customization, contact interactivity, care, community, convenience, cultivation, choice, and character variables on e-loyalty by using gender as a moderating variable. A quantitative method was implemented by having 247 respondents belonging to the millennial category who have made online transactions on the C2C e-commerce platform at least once in the past month. Using the PLS-SEM method, the findings show that customization, contact interactivity, cultivation, community, and convenience can affect e-loyalty on C2C e-commerce platforms. In addition, the research finds that gender can have a moderating effect on customization and community.